P1612CAN THE URINARY NITRATE TO CREATININE RATIO BE USED AS A MARKER FOR KIDNEY TRANSPLANT REJECTION?. (6th June 2020) - Riddell, Amy; Kirkwood, John; Smallwood, Miranda; Winyard, Paul; Knight, Bridget; Steer, Karen; Puddicombe, Lynette; Romanczuk, Lidia; Shore, Angela; Gilchrist, Mark
Abstract: Background and Aims: Early identification and treatment of kidney transplant rejection episodes is vital to limit loss of function and prolong the life of the transplanted kidney and recipient. Current practice depends on detecting a creatinine rise. A biomarker to diagnose transplant rejection, either at an earlier time point, or to inform earlier decision making to biopsy, could be transformative. Urinary nitrate concentration is elevated in renal transplant rejection. Nitrate is a nitric oxide (NO) oxidation product. Transplant rejection upregulates NO synthesis via inducible nitric oxide synthase leading to elevations in urinary nitrate concentration. Historically, assays for measurement of inorganic nitrate in biological fluids have been too time consuming to be useful in a clinical setting. We have recently validated a urinary nitrate concentration assay which could provide results in a clinically relevant timeframe. Our aim was to determine whether urinary nitrate concentration is a useful tool to predict renal transplant rejection in the context of contemporary clinical practice. Method: We conducted a prospective observational study, recruiting renal transplant participants over an 18 month period. We made no alterations to the patients' clinical care including medications, immunosuppression, diet and frequency of visits. We collected urine samples from every clinical attendance including routine attendances, unscheduled attendances for acute clinical indications, and on the day of attendance for biopsy, for those who underwent biopsy. We measured the urinary nitrate to creatinine ratio (uNCR) between patient groups including routine attendances, biopsy proven rejection and biopsy proven "no rejection". uNCR was examined over time for those with transplant rejection. Groups were compared using a 2 tail t-test of unequal variance, for statistical significance. Results: A total of 2656 samples were collected. uNCR during biopsy proven rejection, median 49 µmol/mmol, IQR 23-61, was not significantly different from that of routine samples, median 55 µmol/mmol, IQR 37-82 (p=0.56), or biopsy proven "no rejection", median 39 µmol/mmol, IQR 21-89, (P=0.77). Overall uNCR was highly variable; median 52 µmol/mmol, IQR 31-81, with no diagnostic threshold for kidney transplant rejection. Furthermore, within-patient uNCR was highly variable over time, and thus it was not possible to produce individualised patient thresholds to identify rejection. Conclusion: The urinary nitrate to creatinine ratio is not a useful biomarker for renal transplant rejection.